Country profile – Kenya: Gender, climate change, and nutrition linkages - Mawia, Harriet; Ferguson, Nathaniel; Bryan, Elizabeth; Thomas, Timothy S. (International Food Policy Research Institute, 2025)
Agriculture is vital to Kenya's economy, accounting for 20% of the country’s GDP in 2020. Yet the growth of the sector has slowed in recent years due to unfavorable weather conditions, leading to a reduction in crop and livestock performance (Central Bank of Kenya, 2023). While employment in agriculture has been steadily declining (to 32% in 2023), the sector still employs a large share of the rural population and is the main source of informal employment, rural income, and livelihoods (D’Alessandro et al., 2015; ILO 2025).